2007
DOI: 10.1038/sj.bjc.6604099
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrially targeted ceramide LCL-30 inhibits colorectal cancer in mice

Abstract: The sphingolipid ceramide is intimately involved in the growth, differentiation, senescence, and death of normal and cancerous cells. Mitochondria are increasingly appreciated to play a key role in ceramide-induced cell death. Recent work showed the C16-pyridinium ceramide analogue LCL-30 to induce cell death in vitro by mitochondrial targeting. The aim of the current study was to translate these results to an in vivo model. We found that LCL-30 accumulated in mitochondria in the murine colorectal cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…Microvascular density of each CD31 stained tumor was counted in 10 random high-power fields (Â400) by two investigators blinded with respect to the experimental group. Mitotic figures and Ki-67 positive nuclei were quantified as previously described (21).…”
Section: Methodsmentioning
confidence: 99%
“…Microvascular density of each CD31 stained tumor was counted in 10 random high-power fields (Â400) by two investigators blinded with respect to the experimental group. Mitotic figures and Ki-67 positive nuclei were quantified as previously described (21).…”
Section: Methodsmentioning
confidence: 99%
“…LCL124, alone or in combination with the chemotherapeutic agent gemcitabine, inhibits substantially the growth of human head and neck squamous cell carcinomas in vitro and in vivo (Senkal et al, 2006). LCL30 has potent antitumour activity against colorectal cancer in mice (Dahm et al, 2008).…”
mentioning
confidence: 99%
“…To overcome the low solubility of ceramide, cationic pyridinium ceramide analogues have been developed, which are water soluble . These analogues have effective anticancer activity at relatively low concentrations (Novgorodov et al, 2005;Rossi et al, 2005;Dindo et al, 2006;Senkal et al, 2006;Zeidan and Hannun, 2007;Dahm et al, 2008). LCL124, alone or in combination with the chemotherapeutic agent gemcitabine, inhibits substantially the growth of human head and neck squamous cell carcinomas in vitro and in vivo (Senkal et al, 2006).…”
mentioning
confidence: 99%
“…It is reasonable to predict that cationic ceramides would preferentially accumulate in the mitochondria of cancer cells based on their increased negative charge. Indeed, the efficacy of cationic ceramides on tumor regression has been confirmed in multiple tumor models (Novgorodov et al, 2005;Senkal et al, 2006;Dahm et al, 2008). Specifically, LCL29 and 124 (D-e-and L-t-stereoisomers of C6-CCPS) (Senkal et al, 2006;Szulc et al, 2006) have been shown to have antiproliferative effects in MCF7 and head and neck squamous cell carcinoma (HNSCC) cell lines (Rossi et al, 2005).…”
Section: Introductionmentioning
confidence: 96%